2018
DOI: 10.3847/1538-4357/aac77a
|View full text |Cite
|
Sign up to set email alerts
|

Does Nearby Open Flux Affect the Eruptivity of Solar Active Regions?

Abstract: The most energetic solar flares are typically associated with the ejection of a cloud of coronal material into the heliosphere in the form of a coronal mass ejection (CME). However, there exist large flares which are not accompanied by a CME. The existence of these non-eruptive flares raises the question of whether such flares suffer from a lack of access to nearby open fields in the vicinity above the flare (reconnection) site. In this study, we use a sample of 56 flares from Sunspot Cycles 23 and 24 to test … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 59 publications
(52 reference statements)
1
8
0
Order By: Relevance
“…Observations and numerical modeling of flaring ARs show that, for the failed events, a magnetic flux rope is often trapped in the AR core and does not have an access to open fields (Toriumi et al. 2017b ; Toriumi and Takasao 2017 ; DeRosa and Barnes 2018 ). As the Zeeman Doppler Imaging by Morin et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Observations and numerical modeling of flaring ARs show that, for the failed events, a magnetic flux rope is often trapped in the AR core and does not have an access to open fields (Toriumi et al. 2017b ; Toriumi and Takasao 2017 ; DeRosa and Barnes 2018 ). As the Zeeman Doppler Imaging by Morin et al.…”
Section: Discussionmentioning
confidence: 99%
“…The same mechanism explains the observed result by Toriumi et al (2017b) that the ratio of reconnected flux (in the flare ribbons) to the total AR flux is, on average, smaller for failed events than eruptive cases. DeRosa and Barnes (2018) showed that X-class flares located near coronal fields that are open to the heliosphere are eruptive at a higher rate than those lacking access to open fields.…”
Section: Solar Flares and Cmesmentioning
confidence: 99%
See 1 more Smart Citation
“…Three‐dimensional null points take on a different character according to the eigenvalues of a matrix constructed from the magnetic field in the neighborhood of the null (Parnell et al, ). In the solar magnetic environment, for instance, these eigenvalues would determine whether a separatrix forms a dome which isolates a volume of the magnetic field or the separatrix is oriented vertically such that it forms a boundary between regions of open flux (DeRosa & Barnes, ).…”
Section: Introductionmentioning
confidence: 99%
“…Until now, the key nonpotential parameters of ARs governing the eruptive character of solar flares are still unknown based on statistical results. Moreover, the access to open flux (open to the interplanetary space) is also thought to influence whether an X-class flare is likely to be eruptive (DeRosa & Barnes 2018).…”
Section: Introductionmentioning
confidence: 99%